Coffee quality improvement in Lamdong Province, Vietnam - Bui Hai Nhi; Vincent, Jean Claude; Athapol Noomhorm; Jindal, Vinod Kumar; Swedish International Development Cooperation Agency (Sida) (Bangkok : Asian Institute of Technology, 1997)
This study has main objectives to survey the existing processing patterns and the coffee quality in Vietnamese provinces of Dongnai, Lamdong, Daklak and in a second step to improve the coffee quality produced by the small holders. On the basis of information collected during the survey, experiments about the effects of processing on quality were undertaken in order to determine the more appropriate processes which could be applied to obtain an optimum of quality. · The survey was conducted in 90 farms located in three regions. Two main processes are applied to handle the cherries: sun drying of whole cherries and sun drying of partially pulped cherries. Three kinds of sun drying areas are generally used: cement patio, plastic sheet, and bare earth patio, from which the latter one is dominant (60% to 72%). Percentage of farmers using cement patio is very low (23% to 30%). Although physical and chemical properties of coffee beans are different following the regions, no essential differences in term of cup quality are observed. Four processes including dry process (sun drying of cherries), dry process of partially pulped cherries, wet fermentation process and dry fermentation process were applied to examine their influence on coffee quality. Wet fermentation process (for 24 hours) was found to be the best for ripe and over ripe cherries. Sun drying of red cherries on cement patio or plastic sheet give an acceptable quality. Sun drying of partially pulped cherries could be applied but the quality was not so good compared with samples processed by wet fermentation. Sun drying of cherries should be applied to immature cherries only.
Thesis (M.Sc.) - Asian Institute of Technology, 1997
Keywords: Coffee -- Vietnam -- Lamdong